Technology Readiness and E-Commerce Adoption among Entrepreneurs of SMEs in Bandung City, Indonesia - Astuti, Novika Candra; Nasution, Reza Ashari (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
The emergence of internet-based electronic commerce offers considerable opportunities for companies to expand their customer base, enter new product markets, and rationalize their business. The Indonesian government has initiated and implemented a series of plans and activities to promote technology use to increase SMEsâ performance. Despite such efforts, technology adoption rate are still low. Therefore, it is important to understand the factors affecting an entrepreneursâ decision on internet adoption, by measuring technology readiness (TR). The purpose of this study is to investigate TR and the extent to which E-commerce is adopted amongst entrepreneurs. This study is replication of Parasuramanâs study on the Technology Readiness Index (TRI). Questionnaires were distributed using a convenience sampling method to 190 entrepreneurs of SME in Bandung city. The findings indicate that entrepreneurs are moderate in terms of their TR. There are significant differences in terms of TR across entrepreneursâ backgrounds (gender, age, education, and income). In relation to internet adoption by those surveyed, as their use of media promotion is still low, there were only 36.3 percent who adopted it. The results clearly indicate the need to provide support to SMEs to adopt and use e-commerce. These results have implications not only for managers of SMEs but also for government agencies in developing countries such as Indonesia. The findings have implications for researchers and practitioners by identifying TR drivers (optimism and innovativeness), and barriers (discomfort and insecurity), that contribute to effectively leveraging the Internet in an important area for SMEs.Â Â Â Â Â